PENGARUH TINGKAT KECERDASAN EMOSIONAL TERHADAP PRESTASI AKADEMIK TARUNA MADYA POLITEKNIK ILMU PEMASYARAKATAN - Pido Sodiptas Astanja Girsang; Padmono Wibowo (Sindoro: Cendikia Pendidikan, 2023)
Emotional aspects are very important in influencing the excellence of a student. Many past studies have proven that emotional intelligence affects academic achievement. Therefore, this study is aimed to identify students’ emotional intelligence level and to what extent emotional intelligence influences students’ academic achievement.Given this, the researchers decided to investigate whether the emotional intelligence of Polytechnic associate cadets and academic achievement for achievers are related. In this study 30 cadets used Poltekip class 56 as participants, who were selected using a straightforward random selection methodology. Quantitative research methodology used includes correlation analysis of product moments. The findings showed that Taruna Madya Poltekip Force 56 did not have a positive and significant relationship between emotional intelligence and academic achievement. This relationship is indicated by the correlation coefficient (r) between the variables of self-concept and achievement motivation, which is equal to 0.041 with a value of p 0.295 (p >0.05), which indicates the absence of a significant relationship between variables.